The Study of Financial Supply Chain Management: Challenges and Obstacles - Agarwal, Brijesh Kumar (Journal of Commerce and Trade, 2017)
Supply Chain Financing (SCF) is a product offered by banking sector to realize lower prices for credits. This product is offered to the supplier on the basis of the creditworthiness of the buyer. Credits can therefore been offered at a lower rate of financing than the supplier would be able to negotiate on its own. The goal of working capital management is to keep working capital on an optimal level. This optimal level is the level needed in order to meet the obligations of the company without having excessive levels of cash. Working capital management is concerned with the cash flows moving around the company and it is a big advantage if a company has a clear picture of where funds are required. The present study is a distinct type of work based on secondary information. This is a descriptive work. It discusses various challenges and obstacles which may come in the way of financial supply chain management. Companies can use the financial crisis as an opportunity to rethink their business model. This requires also further development of research in the area of short term financial management and tools for a more accurate risk management. JEL Classification : G 31, G 32.